Fluid dynamic analysis of different Yacht configurations with VOF method - Savino, R; M . Visone; Rossetto, D; D'oriano, V (Fluid dynamics & materials processing, 2015)
This paper presents two applications of Computational Fluid Dynamics (CFD) to super and mega yacht design, based on the Volume of Fluid method. After an overview of recent literature on the subject, the analysis of the hydrodynamic performances of different hull configurations and of different appendage configurations is presented.